1983
DOI: 10.1111/j.1365-246x.1983.tb03319.x
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale gravity profiles across subducted plates

Abstract: The mean gravity profiles, across Central and South America and Eurasia, in the direction normal to the subduction zone are deduced from the Gem 10B gravity model. They have a typical shape: a maximum close to the trench, a negative slope towards the interior of the plate over a 3000 km wide distance, usually followed by a local maximum. It is found that large convective cells driven by the heat sink of the sinking slab have an associated gravity signal having such a typical shape. A detailed comparison betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1983
1983
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…The results shown in Fig. 7 of Parsons & Daly (1984) seem in favour of this generalization but our experiment, for a set of completely different cases, does not (Rabinowicz et al 1983). …”
Section: Ricontrasting
confidence: 53%
See 2 more Smart Citations
“…The results shown in Fig. 7 of Parsons & Daly (1984) seem in favour of this generalization but our experiment, for a set of completely different cases, does not (Rabinowicz et al 1983). …”
Section: Ricontrasting
confidence: 53%
“…1981). It is shown that the shape of the gravity signal associated with these cells can be quite different from that of small aspect ratio cells (Rabinowicz, Lago & Souriau 1983). We showed that the negative admittance values necessary to explain the observed gravity signal landward of the subduction zones can be achieved if some dynamical support is given by convection in the lower mantle.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the mantle, the largest lateral variations in temperature and density are associated with subducted slabs. Numerous studies have shown that subduction zones have a major signature in the geoid [Kaula, 1972;Koyan, 1975;McAdoo, 1981;Jones, 1983;Rabinowicz et al, 1983].…”
Section: Introductionmentioning
confidence: 99%